How to conduct surveys : a step-by-step guide - Fink, Arlene; Kosecoff, Jacqueline B. (Beverly Hills: Sage Publications, 1985)
"Concise and clearly written, this practical guide examines the nuts and bolts of interview and questionnaire design. It takes the reader through the process of deciding informational needs and hypotheses, choosing a questionnaire or interview format, designing a data collection method, choosing a sample, analyzing the findings, and reporting results."--LOC publisher description.
Includes bibliographical references (p. 113) and index.
Keywords: Data Collection -- -- methods; Encuestas educativas; Social surveys; Enqu?etes sociales; Educational surveys; Éducation -- -- Enqu?etes.; Enqu?etes, Méthode des; Enqu?etes sociales; Enqu?etes sociologiques; Sozialstruktur; Umfrage; Erhebungsverfahren; Social surveys - Manuals